166k views
2 votes
У=-3x+3
y = -9x + 15

User Vallerie
by
5.4k points

1 Answer

5 votes

Answer:

(2, - 3 )

Explanation:

Given the 2 equations

y = - 3x + 3 → (2)

y = - 9x + 15 → (2)

Substitute y = - 3x + 3 into (2)

- 3x + 3 = - 9x + 15 ( add 9x to both sides )

6x + 3 = 15 ( subtract 3 from both sides )

6x = 12 ( divide both sides by 6 )

x = 2

Substitute x = 2 into either of the 2 equations and solve for y

Substituting into (1)

y = - 3(2) + 3 = - 6 + 3 = - 3

solution is (2, - 3 )

User Basmah
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.